A Case for More Generous Compensation for Human Research Subjects in Non-Therapeutic Research - Carolyn Chapman (Voices in Bioethics, 2020)
How much payment participants in human research clinical trials should be allowed to receive continues to stir significant debate. Federal regulations state: “An investigator shall seek...consent only under circumstances...that minimize the possibility of coercion or undue influence”.1 When surveyed, Institutional Review Board (IRB) members and human subjects protection professionals “indicated considerable ethical concern that payment could constitute coercion or undue inducement”.2 Although historically viewed with misgiving, compensating research subjects is both acceptable and ethically warranted by the principles of autonomy, non-maleficence, beneficence and justice, particularly in non- therapeutic research. Although current guidelines stress the dangers of paying research subjects too much, we should be more concerned about whether we are paying them too little.